Level of Knowledge among Mother’s Uses of ORS Therapy in Diarrhea Under 5 Years of Children - Roomana Qureshi, Fozia Baloch, Naheed Haroon Kazi, Imtiaz Qureshi, Tasneem Kousar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine mothers’ knowledge regarding ORS therapy during diarrhea among children, aged under five years. Methodology: This was a cross-sectional study and was conducted at the pediatric department of Bilawal Medical College for Boys LUMHS/Jamshoro. The study duration was six months, from March 2021 to August 2021. All the mothers, aged 18 to 40 years, who presented with their children under 5 years old with acute diarrhea and were willing to participate in the study were included. After taking demographic information, interviews were conducted with the mothers, and data was gathered. A self-structured questioner was used to assess the maternal knowledge in terms of diarrhea and its severity, the purpose of ORS, the ORS preparation method, the frequency of use, and the type of ORS. All the data was collected via a study proforma, and SPSS version 26 was used for the data analysis. Results: Children’s mean age was 4.0+2.58 years. Most of the children 60.5% were girls and 38.3% were boys. The majority of women, 43.2%, were educated; 30.9% had a secondary education; 21% had a primary education; and only 4.9% were graduates. Majority of the individuals 75.3% belongs to poor socioeconomic status. Overall, 82.7% of mothers were aware of the severity of diarrhea, 91.4% were aware of ORS, 61.7% believed it was used to prevent water loss, 4.9% believed it prevented salt and water imbalances, and 4.9% believed it was used to prevent diarrhea, while 28.4% were unaware. 69.1% of mothers were aware of the ORS preparation method, but 56.8% had no idea how long ORS should be used for. 49.4% of mothers said ORS should be used slowly at small intervals, few said as per demand; and the remaining had no knowledge. Although regarding types of ORS, most of the mothers 71.6% had no idea. Conclusion: As per the study conclusion, most of the mothers had inadequate knowledge of ORS therapy during diarrhea. Numerous factors, including lower socioeconomic status, maternal illiteracy, caregiver ignorance, and the inability to offer therapy, when necessary, are linked to the severity of disease. Keywords: Diarrhea, ORS, Dehydration, knowledge, Mothers